2013
DOI: 10.1021/ic400015v
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Inertness of Copper(II) Chelates of Cyclen-Based Macrobicycles with Two trans-N-Acetate Arms

Abstract: Two cross-bridged cyclen-based macrocycles with two trans-N-acetic acid arms, one having a dibenzofuran (DBF) moiety as the bridge, H2L1, and the other a diphenyl ether (DPE) one, H2L2, were synthesized. Both compounds behave as "proton sponges." The thermodynamic stability constants for the Cu(2+), Zn(2+), Al(3+), and Ga(3+) complexes of both compounds were determined. They exhibit an excellent thermodynamic selectivity for copper(II), ensuring that metal ions largely present in the human body do not interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 79 publications
3
47
0
Order By: Relevance
“…Recently published work on new Cu(II) chelators has shown that highly inert Cu-complexes can be obtained by modification of CB-TE2A-type structures, either by extension of the cross-bridge 20 or integration of a donor atom into the cross bridge. 21 We also took the potent copper chelator cyclam as a base and used the previously established synthesis of 1,8-(2,6-Pyridinedimethylene)-1,4,8,11-tetraazacyclo-tetradecane (here abbreviated as pycup) by Brandes et al, 22 to furnish ligand that incorporates a pyridyl nitrogen donor atom into the cross-bridge. Incorporation of this donor group for the purpose of building a more sturdy ligand is based on the well-documented preference of Cu(II) for softer nitrogen donors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently published work on new Cu(II) chelators has shown that highly inert Cu-complexes can be obtained by modification of CB-TE2A-type structures, either by extension of the cross-bridge 20 or integration of a donor atom into the cross bridge. 21 We also took the potent copper chelator cyclam as a base and used the previously established synthesis of 1,8-(2,6-Pyridinedimethylene)-1,4,8,11-tetraazacyclo-tetradecane (here abbreviated as pycup) by Brandes et al, 22 to furnish ligand that incorporates a pyridyl nitrogen donor atom into the cross-bridge. Incorporation of this donor group for the purpose of building a more sturdy ligand is based on the well-documented preference of Cu(II) for softer nitrogen donors.…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum of Cu 2 L1 is quite different from that of Cu 1 L1 and is best simulated with three components: 48 % of component A with g ∥ = 2.202, A ∥ = 554 MHz, g ⊥ = 2.056, and A ⊥ = 47 MHz similar to the spectrum of Cu 1 L1 , 12 % of component B with g ∥ = 2.416, A ∥ = 389 MHz, g ⊥ = 2.0832, and A ⊥ = 14.5 MHz, and 40 % of a broad component C with g ∥ = 2.262, A ∥ = 178 MHz, g ⊥ = 2.0480, and A ⊥ = 7.5 MHz and H‐strain broadenings in the order of 400 MHz (Figure C). The second component with relatively large g ∥ would indicate coordination to four oxygen ligands according to the Peisach–Blumberg rules if it could be considered to have only four ligands but this is unlikely for Cu II –cyclen complexes as seen from recent structural data of similar complexes , . It only accounts for 12 % of the spectral intensity and was included in the simulation because it was quite pronounced in the echo‐detected field sweep spectra of the same sample (cf.…”
Section: Resultsmentioning
confidence: 99%
“…Figure S2 ( transfer transition (LMCT) is observed at 368 nm (ε = 7600 L mol -1 cm -1 ) for 1, 374 nm (ε = 10500 L mol -1 cm -1 ) for 2, and 371 nm (ε max = 13700 L mol -1 cm -1 ) for 3. 26 Interestingly the other ligand based strong absorption bands were seen at 259 nm with ε values of 3510, 52400…”
Section: Powder X-ray Diffraction Patternsmentioning
confidence: 99%